TRADISI BERSIH DESA DI LERENG GUNUNG BROMO - Rita Istari (BRIN, 2009)
Bersih Desa tradition in Pusungmalang, Puspo, Pasuruan is one among various ritual worships. The purpose is to ask for a savety over the danyang in the village. The existence of this tradition cannot be separated from its environment because they are interconnected to each other. The tradition occurs in Javanese people where animism elements are still influenced their mindset, ideology as well as their daety routinity. The Javanese people believed in mystic world or supranatural where every objects regarded as having its own spirit. Pusungmalang which consists of five villages, still keeps the harmonious relationship between humans and their nature. They believed if a violation occurs then disaster would come.